ANALISIS SEMIOTIKA BILLBOARD SETENGAH JADI DARI KITKAT BERJUDUL “BREAK” OLEH JWT LONDON - Fernando, Vito; muhammad adi sukma nalendra (JURNAL RUPA MATRA, 2024)
Billboards or advertising billboards are advertising media placed on large boards positioned strategically. They usually contain visuals or messages that attract attention to promote products, services, or specific messages to the audience. One of the attention-grabbing billboards is the KitKat brand advertisement titled "Break" produced by JWT London in October 2014. This research aims to conduct semiotic analysis of this advertisement to understand the messages conveyed through its visual elements and the use of environmental media. The analysis uses a qualitative method employing Roland Barthes' semiotic theory to explore the meanings within the advertisement. It examines how images, words, and their application communicate the KitKat product. This study helps understand how the advertisement communicates messages and how the advertisement's messages influence the audience.